Relevance of Independent Educatıonal Actıvıtıes of Students ın the Credit–Modular Education System - Malikova Muhabbat; Bozorova Aziza; Sayfullayeva G. I. (Open Academia, 2023)
The"concept for the development of the higher education system of the Republic of Uzbekistan until 2030" sets out specific tasks for introducing digital technologies and modern teaching methods to higher education processes, broad involvement of young people in scientific activities, combating corruption, increasing the proportion of students studying in engineering and technical education areas, introducing a credit-module system, increasing the practical share of According to the "concept of development of the higher education system of the Republic of Uzbekistan until 2030"approved by the decree of the president of the Republic of Uzbekistan dated October 8, 2019, 85% of higher education institutions in the country are planned to be transferred to the credit-modular system in stages until 2030. This is an activist in the credit-modular system of almost all higher education institutions in the country for the coming years
Keywords: credit-module system; education; process